Persepsi Wisatawan Domestik terhadap Autentisitas Batik di Pasar Beringharjo - Hanin Banurukmi (Gadjah Mada Journal of Tourism Studies, 2022)
Aside from maintaining its function as a traditional market, Pasar Beringharjo also serves as a batik-shopping destination for tourists who visit Yogyakarta. However, Batik(s) originated from Yogyakarta are not the only ones that can be found here, as other regions' Batik can also be obtained in Beringharjo. This indeed is a contradicting situation as souvenirs produced by local craftsmen embody important values for tourists. This study attempts to figure out how domestic tourists perceive the authenticity of batik in Beringharjo. Through the descriptive-qualitative study, 11 informants from various regions in Indonesia, except Daerah Istimewa Yogyakarta province, were interviewed with a semistructured technique. The interview questions were developed from the adaptation of the souvenir authenticity theory by Littrell, Anderson, and Brown (1993: 204-207). The results indicate that domestic tourists perceive the authentic Yogyakarta batik as batik that does not originate from other regions; has high-quality materials; can not be bought in other regions; is made with the traditional "canting tulis" method; has unique characteristics; and uses the original colors of Yogyakarta.